Konsep Pendidikan Tauhid dalam Surat Al Ikhlas Ayat 1-4 - Nasikhatul Kharimah; Faisal Kamal; Ali Imron (Islah Tarbawi: Journal of Islamic Education and Learning, 2026)
Tauhid education serves as the fundamental basis for developing students’ faith, belief, and moral character. Surah Al-Ikhlas is one of the Qur’anic chapters that presents the concept of monotheism in a concise yet comprehensive manner, making it highly relevant to Islamic education. This study aims to analyze the concept of tauhid education contained in Surah Al-Ikhlas verses 1–4 and to examine its educational messages from an Islamic perspective. The research employed a qualitative approach using a library research method. Data were collected from the Qur’an, tafsir literature, Islamic education references, scientific journals, and other relevant sources through documentation techniques. The data were then analyzed using descriptive-analytical methods. The findings reveal that Surah Al-Ikhlas contains essential principles of tauhid education, including belief in the absolute Oneness of Allah (Tawhid Uluhiyyah), belief that Allah is the sole Creator and Sustainer of the universe (Tawhid Rububiyyah), and belief in Allah’s perfect names and attributes (Tawhid Asma’ wa Sifat). The surah emphasizes that Allah is One, the Eternal Refuge upon whom all creation depends, neither begets nor is born, and that nothing is comparable to Him. These values contribute significantly to strengthening students’ faith, piety, sincerity, and noble character. Therefore, Surah Al-Ikhlas can serve as a foundational framework for Islamic education aimed at reinforcing faith and cultivating Islamic character in daily life.